Current trends of natural processes in Polar Regions of the Earth and prospects for the Russian polar research: The 11th conference in Sochi - M. Yu. Moskalevsky (Лëд и снег)
On 5–7 October 2015 the All-Russian scientific conference «Results and prospects of studying natural environment in the Russian Arctic and other polar regions» was held in Sochi (south Russia). The conference was attended by about 80 scientists from different organizations of Russia. The reports presented the results of investigations performed during the last years. This review summarizes the main ideas and results of research in the field of glaciology and permafrost studies of the Arctic.